Las juntas patrióticas de españoles en México ante el 98: patriotismo, disidencia y proselitismo político - Granados, Aimer (El Colegio de México, A.C., 2000)
This paper reviews the political activities of the Spanish colony in Mexico during the Porfiriato, regarding the 1895-1898 war between Spain and Cuba and the United States. The author focuses on three urban centers with Spanish residents -Mexico City, Veracruz and Merida- and analyzes the subject in relation with the colony's complex ideological, social and material interests. The patriotic activities carried out by the colony until the defeat of 1898 is not explained from the diplomatic viewpoint, which is the most common, but from the creation of  patriotic groups (juntas patrióticas), encouraged by the Spanish embassy and  by institutions such as the Casino, the interests of which were often contrary to those of the Mexican government and even entailed conflicts with Cuban secessionist groups also active in Mexico.